(untitled) (Archives of Criminology, 2024)
The aim of this article is to characterize the sexual behavior of women committing sex crimes and to determine the possible similarities and differences in the criminal activity of female perpetrators of such crimes. The study is theoretical in nature and is based on the literature review method. The research findings made it possible to conclude that the criminal activity of women in terms of sex offenses does not differ significantly from similar behavior by men. Women engage in the most brutal sex crimes, including rape and sexual murder, both alone and with other people of both sexes. Very often, they also initiate these acts, which contradicts the belief that they are passive participants. The victims include both family members and those outside the family circle, although in the case of the perpetrator–victim relationship, women are more likely to harm people they know and with whom they have had some relationship. Women use violence no less than men. Even if they themselves do not directly contribute to extreme injuries or even the death of the victim, they do not discourage their accomplices from such behavior and, on the contrary, repeatedly encourage them to commit cruel acts.